Rendahnya Kesejahteraan Guru - Siti Sovia; Pausan Asima; Haryanti Sapitri Yanti; Widya Julita (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Teacher welfare in Indonesia is a critical issue affecting national education quality. Many teachers, especially in remote areas and private schools, suffer from low salaries, inadequate facilities, and excessive workloads, often necessitating additional jobs. Insufficient government support in allowances, incentives, and professional development exacerbates these challenges, leading to decreased teacher motivation and performance. This results in poor teaching quality and hinders student development, impacting both individual potential and national productivity. Addressing this requires strategic solutions such as improved government policies, increased education budgets, and sustainable professional development programs. Fair salary standards, transparent allowance distribution, and teacher involvement in policy-making are crucial. Enhancing facilities, reducing administrative burdens, and fostering a supportive work environment are also essential. By prioritizing teacher welfare, Indonesia can improve educational outcomes and ensure a more sustainable future.